POSTSTRUCTURALISM AND ITS PRACTICAL RELEVANCE IN INTERNATIONAL POLITICS - Rifki Dermawan (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2019)
There are many different theories and approaches in international relations studies. They emerge as tools to understand world politics as well as to prevent the occurrence of wars and conflicts. Poststructuralism is one of them. This article addresses the practical relevance of poststructuralism in international politics. It looks at the role of poststructuralism, which provides a novel view on international issues in the globalized era. There are three major focuses of this paper. First, the discussion on the concept of sovereignty and state in a modern world. Second, the role of discourse in the poststructuralism theoretical framework. Third, the function of poststructuralism as a meta-theoretical critique in international relations. This article concludes that poststructuralism is practically useful in the study of international politics. Keywords: poststructuralism, theory, international politics, international relations. Abstrak Ada beragam teori dan pendekatan yang digunakan di dalam studi ilmu hubungan internasional. Teori dan pendekatan tersebut muncul sebagai alat untuk memahami kondisi peepolitikan dunia dan juga untuk mencegah terjadinya peperangan dan konflik. Poststrukturalisme adalah salah satunya. Tulisan ini membahas relevansi secara praktikal dari poststrukturalisme dalam politik internasional. Tulisan ini melihat peranan poststrukturalisme yang memberikan pandangan baru terhadap isu-isu internasional di zaman globalisasi. Ada tiga fokus utama dari tulisan ini. Pertama, pembahasan mengenai konsep kedaulatan dan negara di zaman modern. Kedua, peranan wacana dalam kerangka teori poststrukturalisme. Ketiga, fungsi poststrukturalisme sebagai kritik metateori di ilmu hubungan internasional. Kesimpulan yang dapat diambil dari tulisan ini adalah poststrukturalisme memiliki manfaat secara praktikal dalam studi politik internasional. Kata kunci: poststrukturalisme, teori, politik internasional, ilmu hubungan internasional.